2024
DOI: 10.1021/acs.energyfuels.4c00507
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on the Macroscopic Exploitation and Microscopic Mobilization Characteristics of CO2 and N2 HnP to Enhance Shale Oil Recovery

Feng Liu,
Yong Kang,
Mengda Zhang
et al.

Abstract: Gas huff and puff (HnP) is one of the means to improve shale oil recovery, and the commonly used gases are CO 2 and N 2 . However, the current research on CO 2 and N 2 HnP enhancing shale oil recovery is not sufficient. This study compares the macroscopic exploitation and microscopic mobilization characteristics of CO 2 and N 2 HnP by the HnP experiments with a full-diameter core, gas chromatography−mass spectrometry (GC-MS) tests, and online nuclear magnetic resonance (NMR) tests. Moreover, the impact of cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Relevant investigations have shown that supercritical carbon dioxide (SC-CO 2 ) can significantly enhance the recovery of shale reservoirs. When the pressure and temperature of CO 2 reach a certain condition (generally P ≥ 7.38 MPa, T ≥ 31.1 °C), it will enter the supercritical phase. Thanks to its high density, minimal viscosity, and excellent diffusivity, supercritical carbon dioxide (SC-CO 2 ) easily mixes with crude oil and can effectively lower its viscosity. This makes it easier for more shale oil to flow to the wellbore and efficiently enhances the recovery. , Meanwhile, CO 2 used can also be sequestered in shale reservoirs in the form of dissolution, trapping, and mineralization. …”
Section: Introductionmentioning
confidence: 99%
“…Relevant investigations have shown that supercritical carbon dioxide (SC-CO 2 ) can significantly enhance the recovery of shale reservoirs. When the pressure and temperature of CO 2 reach a certain condition (generally P ≥ 7.38 MPa, T ≥ 31.1 °C), it will enter the supercritical phase. Thanks to its high density, minimal viscosity, and excellent diffusivity, supercritical carbon dioxide (SC-CO 2 ) easily mixes with crude oil and can effectively lower its viscosity. This makes it easier for more shale oil to flow to the wellbore and efficiently enhances the recovery. , Meanwhile, CO 2 used can also be sequestered in shale reservoirs in the form of dissolution, trapping, and mineralization. …”
Section: Introductionmentioning
confidence: 99%